2003
DOI: 10.1128/mcb.23.7.2489-2500.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Basic Transcription Element Binding Protein by Gene Targeting Technology

Abstract: Basic transcription element binding protein (BTEB) is a transcription factor with a characteristic zinc finger motif and is most remarkably enhanced by thyroid hormone T 3 treatment (R. J. Denver et al., J. Biol. Chem. 272:8179-8188, 1997). To investigate the function of BTEB per se and to touch on the effects of T 3 (3,5,3-triiodothyronine) on mouse development, we generated BTEB-deficient mice by gene knockout technology. Homologous BTEB؊/؊ mutant mice were bred according to apparently normal Mendelian genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 34 publications
0
61
1
1
Order By: Relevance
“…Klf9/Bteb1 mutant mice (Bteb1 lacZ ) were generated by insertion of the bacterial ␤-galactosidase (LacZ) gene in-frame into the first exon of the mouse Bteb1 gene as described previously (23). Mice were genotyped by PCR of genomic DNA prepared from mouse tails by overnight digestion at 55°C in Tris-HCl buffer containing Triton X-100 (0.5%) and proteinase K (50 g/ l).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Klf9/Bteb1 mutant mice (Bteb1 lacZ ) were generated by insertion of the bacterial ␤-galactosidase (LacZ) gene in-frame into the first exon of the mouse Bteb1 gene as described previously (23). Mice were genotyped by PCR of genomic DNA prepared from mouse tails by overnight digestion at 55°C in Tris-HCl buffer containing Triton X-100 (0.5%) and proteinase K (50 g/ l).…”
Section: Methodsmentioning
confidence: 99%
“…Because currently available anti-BTEB1 antibodies, including ours, have so far given high nonspecific staining in immunohistochemical studies of mouse tissues (data not shown), we took advantage of the functional ␤-galactosidase gene that was inserted into exon 1 of the Bteb1 gene to determine endogenous sites of Bteb1 expression in the early pregnant uterus. A previous study (23) demonstrated that X-gal staining of various tissues from Bteb1 ϩ/lacZ mice recapitulates the endogenous expression pattern of the Bteb1 gene. X-gal stained-cryosections of uterine tissues isolated from Bteb1 ϩ/lacZ mice at 0.5, 3.5, and 6.5 dpc revealed the distinct cell type localization of this gene (Fig.…”
Section: Increased Incidence Of Neonatal Lethality For Bteb1 ϫ/ϫmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteínas obtidas a partir de indústrias de óleos vegetais em são mais suscetíveis à contaminação por Salmonella spp. (Morita et al, 2003;European Food Safety Authority, 2006). …”
Section: Ingredientes Para Alimentação Animal E Contaminaçãounclassified